Mengonstruksi Masa Depan Indonesia: Situasi Retorikal tentang Ibu Kota Negara Nusantara - Andika Hendra Mustaqim (Program Studi Komunikasi Penyiaran Islam Fakultas Dakwah dan Komunikasi, 2022)
The purpose of this study is to explore the elements of the rhetorical situation in President Joko Widodo's (Jokowi) speech or statement relating to the Capital City of Nusantara(IKN) of the Archipelago. The research method adopted is rhetoric with a qualitative approach based on text and video. This study finds that Jokowi develops elements of a rhetorical situation starting from urgency, audience, and tension. Apart from that, other elements are social problems, situational relations, and context expansion. The six elements of the rhetorical situation show how President Jokowi is struggling to realize IKN Nusantara as part of the construction of Indonesia's future. In terms of President Jokowi's rhetorical situation strategy regarding IKN Nusantara, he uses a persuasive, deliberative, exemplary, and argumentative approach. Research has a real theoretical impact because it participates in developing and applying rhetorical situation theory. In addition, this research also has a very real impact in terms of practicality because it can be used as reference material and consideration by government leaders in formulating rhetoric in making statements or speeches